Pengembangan Circulatory System Mobile Learning (CSML) untuk Siswa Kelas XI - Kumalasari, Anggi Prastiwi; Harlita; Rinanto, Yudi (Biosfer: Jurnal Pendidikan Biologi, 2024)
The utilization of communication devices such as mobile phones as a learning support tool in the development of technology 4.0 is still low. The low mobile phone utilization as a learning support tool causes the variety of learning media used by teachers to be low. The low variety of learning media results in students having difficulty mastering the concept of learning material, especially circulatory system material in class XI. The difficulty of concept mastery on circulatory system material can be overcome through the development of circulatory system mobile learning (CSML). The research objectives are: 1) Develop CSML on circulatory system material in grade XI, 2) Test the feasibility of CSML, and 3) Know the response of teachers and students to CSML. The type of research is Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection uses feasibility validation questionnaires  and response questionnaires. The data analyzed were the results of the feasibility assessment from media experts and material experts, and the results of responses from teachers and students. Data analysis was carried out quantitatively descriptive using a Likert scale of 1-4. The results of the study are 1) The result of developing CSML can be accessed online; 2) The results of the feasibility assessment from media experts were 82.27% and material experts were 89.59% with a very feasible category; 3) The results of teacher responses were 87.02% and student responses were 88.55% with a great category.